2016
DOI: 10.19180/1809-2667.v18n32016p97-105
|View full text |Cite
|
Sign up to set email alerts
|

Perda de massa de frutos de cultivares de morangueiro em diferentes condições e tempos de armazenamento

Abstract: A cultura do morango é considerada de clima temperado e possui grande aceitação no mercado apresentando excelentes características organolépticas que agradam o consumidor, podendo-se destacar a cor vermelha brilhante intensa, odor envolvente, Perda de massa de frutos de cultivares de morangueiro em diferentes condições e tempos de armazenamento

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…The loss of mass recorded in this work is below that mentioned by Hernández-Muñoz et al (2006) as harmful to fruit quality (10%) and equivalent to that reported by Ávila et al (2012) in a cold room trial at 1 ± 0.5 °C and 90-95% relative humidity with values of 8.93% and 9.49% in the cultivars Camino Real and Camarosa, respectively. Guimaraes et al (2017), at the end of 12 days of refrigerated storage, they found losses ranging from 0.85 to 2.13%, which can be explained by the use of a Styrofoam tray and 15µ PVC film, which reduced the loss of water, providing longer shelf life.…”
Section: Discussionmentioning
confidence: 99%
“…The loss of mass recorded in this work is below that mentioned by Hernández-Muñoz et al (2006) as harmful to fruit quality (10%) and equivalent to that reported by Ávila et al (2012) in a cold room trial at 1 ± 0.5 °C and 90-95% relative humidity with values of 8.93% and 9.49% in the cultivars Camino Real and Camarosa, respectively. Guimaraes et al (2017), at the end of 12 days of refrigerated storage, they found losses ranging from 0.85 to 2.13%, which can be explained by the use of a Styrofoam tray and 15µ PVC film, which reduced the loss of water, providing longer shelf life.…”
Section: Discussionmentioning
confidence: 99%